Hard power e soft power na realidade e na memória da Itália de Mussolini - Richard Bosworth (Estudos do Século XX)
Benito Mussolini was appointed Prime Minister of Italy by King Victor Emmanuel III on 30 October 1922. His regime soon back-dated itself by a couple of days, proclaiming the Fascist ‘March on Rome’ had brought ‘revolution’ to Italy on 28 October. On 3 January 1925 Mussolini spoke decisively to the Chamber of Deputies refusing to apologise for his followers’ violence.[1]  It had been especially manifested in the kidnapping and murder of the moderate socialist deputy, Giacomo Matteotti, seized from the streets of Rome on 10 June 1924. That oration and the repression of opposition press and persons which directly followed it are generally accepted as the moment when the Duce or DUCE (Leader) as he was now always known, became a fully-fledged dictator.[2]  Mussolini held office until 25 July 1943 when, given the disasters of Italy’s Second World War, entered on the Nazi German side on the ill-omened date of 10 June 1940, he was dismissed by the King and then arrested.